Undergraduate Thesis Manual: Techniques and Skills for Success (RIAF. International Journal of Physical Activity, 2026)
This manual offers a structured guide for developing undergraduate theses, covering topics from theme selection to the final document presentation. Its purpose is to provide students with a clear methodological framework, ensuring academic rigor and compliance with institutional standards. The introduction emphasizes the importance of a systematic process, while the core sections detail key elements such as theoretical and methodological frameworks, and results analysis, adaptable to qualitative, quantitative, or mixed approaches. The methodology focuses on research designs, data collection techniques (surveys, interviews, observation), and analysis tools (statistical or thematic), supported by practical examples and updated references. The conclusions highlight the manual’s role in standardizing thesis quality, avoiding common pitfalls, and saving researchers’ time. It also includes evaluation rubrics and templates to ensure coherence and originality. This resource is indispensable for students aiming to produce robust and applicable academic contributions in their fields.
Keywords: Bachelor's thesis; Manual; Research skills